Multifunctional Nanoparticles Based on Iron Oxide and Gold-198 Designed for Magnetic Hyperthermia and Radionuclide Therapy as a Potential Tool for Combined HER2-Positive Cancer Treatment - Michał Żuk; Rafał Podgórski; Anna Ruszczyńska; Tomasz Ciach; Agnieszka Majkowska-Pilip; Aleksander Bilewicz; Paweł Krysiński (MDPI AG, 2022)
Iron oxide nanoparticles are commonly used in many medical applications as they can be easily modified, have a high surface-to-volume ratio, and are biocompatible and biodegradable. This study was performed to synthesize nanoparticles designed for multimodal HER2-positive cancer treatment involving radionuclide therapy and magnetic hyperthermia. The magnetic core (Fe3O4) was coated with a gold-198 layer creating so-called core-shell nanoparticles. These were then further modified with a bifunctional PEG linker and monoclonal antibody to achieve the targeted therapy. Monoclonal antibody-trastuzumab was used to target specific breast and nipple HER2-positive cancer cells. The nanoparticles measured by transmission electron microscopy were as small as 9 nm. The bioconjugation of trastuzumab was confirmed by two separate methods: thermogravimetric analysis and iodine-131 labeling. Synthesized nanoparticles showed that they are good heat mediators in an alternating magnetic field and exhibit great specific binding and internalization capabilities towards the SKOV-3 (HER2 positive) cancer cell line. Radioactive nanoparticles also exhibit capabilities regarding spheroid degradation without and with the application of magnetic hyperthermia with a greater impact in the case of the latter. Designed radiobioconjugate shows great promise and has great potential for in vivo studies regarding magnetic hyperthermia and radionuclide combined therapy.